2017
DOI: 10.1002/pon.4525
|View full text |Cite
|
Sign up to set email alerts
|

Educational and vocational goal disruption in adolescent and young adult cancer survivors

Abstract: The physical and cognitive impacts of treatment can make returning to school/work challenging for AYA cancer survivors. Adolescents and young adults experiencing difficulties may benefit from additional supports to facilitate meaningful engagement with their chosen educational/vocational goals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 45 publications
6
59
0
Order By: Relevance
“…Vetsch et al . () and Bellizzi et al . () found similar positive shifts in life goals and priorities after cancer treatment for YACS, while Park and Blank () found no such changes.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Vetsch et al . () and Bellizzi et al . () found similar positive shifts in life goals and priorities after cancer treatment for YACS, while Park and Blank () found no such changes.…”
Section: Discussionmentioning
confidence: 84%
“…They experienced a changed perspective including appreciating everyday life more, taking nothing for granted and using their time wisely to follow their dreams. Vetsch et al (2018) and Bellizzi et al (2012) found similar positive shifts in life goals and priorities after cancer treatment for YACS, while Park and Blank (2012) found no such changes.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Their cancer diagnoses and treatments significantly disrupt their developmental trajectories and construction of personal identity in crucial areas such as education, career, and social relationships. [2][3][4][5] After treatment, they face multifaceted survivorship issues including fatigue, 6,7 psychosocial problems, 8 and practical financial concerns [9][10][11] that can greatly impede their transition back to work or school. 12 A growing body of literature has elucidated AYA cancer survivors' diverse needs.…”
Section: Introductionmentioning
confidence: 99%